Complete chloroplast genome sequence of Punica granatum ‘Nana’ (Lythraceae) and phylogenetic analysis - Jie Wang; Zhi-Qiang Wu; Li Ma; Cui-Hua Gu (Mitochondrial DNA. Part B. Resources, 2020)
Pomegranate (Punica granatum L.) is of great significance both as a fruit tree and an ornamental plant. Hereon, we sequenced and characterized the complete chloroplast genome of Punica granatum ‘Nana’ and performed phylogenetic analysis concerning related species. It turned out that the length of chloroplast genome sequence reached 158,639 bp and exhibited a four-conjoined structure, i.e., a large single copy region (LSC, 89,022 bp), a small single copy region (SSC, 18,685 bp) and twain inverted repeat regions (IRa and IRb, 25,466 bp). 112 unique genes were identified, consisting of 78 protein-coding genes, four ribosomal RNA (rRNA) genes and 30 transfer RNA (tRNA) genes. The result of phylogenetic analysis based on Neighbor-joining (NJ) method was consistent with that of Bayesian inference (BI), which strongly supported that Punica granatum ‘Nana’ was close to its original species Punica granatum and they together had a close relationship with Heimia myrtifolia within Lythraceae.